If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 4 = x + -11 Reorder the terms: 4 + 9x = x + -11 Reorder the terms: 4 + 9x = -11 + x Solving 4 + 9x = -11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + 9x + -1x = -11 + x + -1x Combine like terms: 9x + -1x = 8x 4 + 8x = -11 + x + -1x Combine like terms: x + -1x = 0 4 + 8x = -11 + 0 4 + 8x = -11 Add '-4' to each side of the equation. 4 + -4 + 8x = -11 + -4 Combine like terms: 4 + -4 = 0 0 + 8x = -11 + -4 8x = -11 + -4 Combine like terms: -11 + -4 = -15 8x = -15 Divide each side by '8'. x = -1.875 Simplifying x = -1.875
| x^2+5x=48 | | x^2+3-28=0 | | 4x+3x=7x+12 | | 6w-9w=9 | | 12-3x=10x-45 | | y=-10*1+1 | | y=-10*0+1 | | (x+1)(2x+5)=(2x+3)(x-4)+5 | | 3x^2+14xy+8y^2=0 | | 6x^2+14xy+8y^2=0 | | y=-10*-1+1 | | (2x+9)(7x-9)= | | 16=p/4+10 | | C^2=5c | | (+3)+(-7) | | y=-10*-5+1 | | 5m-9=8m+9 | | 9x+2=6x+38 | | (2x+9)(7x-9)=0 | | 6x^2-14xy+8y^2=0 | | 2(y+5)+2(x+5)= | | 4m^2-27m-40=0 | | x+(x*3)=36 | | 3x^2+36x+21=0 | | 4x^2+31x+42=0 | | 6x-9=6x+12 | | na=b | | (x+4)(x+13)=0 | | 52-20/3x4+9x2= | | (x-8)(x+4)=0 | | an=b | | (4-5x)(4x-5)=(10x-3)(7-2x) |